Marine macroalgae as a feasible and complete resource to address and promote Sustainable Development Goals (SDGs) - García Poza, Sara; Pacheco, Diana; Cotas, João; Marques, João C.; Pereira, Leonel; Gonçalves, Ana M. M. (Integrated Environmental Assessment and Management, 2022)
Because the world's population is increasing, science‐based policies are needed to promote sustainable global development. It is important to maintain and restore the environment and help human society overcome the risks from industrialization and unsustainable exponential growth. In recent years, many studies have highlighted that macroalgae represent a key marine resource for ecological and sustainable living, thus helping to address today's global problems, such as water pollution, ocean acidification, and global warming. Macroalgae show the potential to provide innovative, ecofriendly, and nutritious food sources and natural compounds for various industries, such as biomedical, food, agricultural, and pharmaceutical industries. This review discusses how macroalgae can help us today and how they can promote a more sustainable way of life in the future. It also discusses the potential danger for ecosystems and the global population if these organisms are not part of the solution but part of the problem. 1161 1148 14